TRANFORMASI SOSIAL, HUKUM, PEMBANGUNAN DAN MODERNISASI MASYARAKAT - Rohadi Rohadi; Tri Budi Prasetyo (Universitas Muhammadiyah Ponorogo, 2020)
Social transformation, law, development and modernization involve human history. In this context, law in Indonesia is a cultural phenomenon and can be studied with the approach of cultural science, law and methodological tools. With its advantages and disadvantages, studies on social transformation, law, development and modernization towards progress and a better government order towards civil society. As the background of the Paradigm of Social Transformation, Law, Development and Modernization of Society, which is the discussion in this proposal, it is attempted to be able to distance itself from the attitudes Richard C. Martin called as fideistic subjectivism or scientific objectivity. More importantly, the side that portrays the side of the government towards the weak or the poor and becomes an important awareness that is critical of the existence of social transformation, law, development and community modernization.